2021
DOI: 10.1371/journal.ppat.1010069
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of inflammatory arthritis by the parasitic worm product ES-62 is associated with epigenetic changes in synovial fibroblasts

Abstract: ES-62 is the major secreted protein of the parasitic filarial nematode, Acanthocheilonema viteae. The molecule exists as a large tetramer (MW, ~240kD), which possesses immunomodulatory properties by virtue of multiple phosphorylcholine (PC) moieties attached to N-type glycans. By suppressing inflammatory immune responses, ES-62 can prevent disease development in certain mouse models of allergic and autoimmune conditions, including joint pathology in collagen-induced arthritis (CIA), a model of rheumatoid arthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 97 publications
1
12
0
Order By: Relevance
“…We chose the Collagen-Induced Arthritis (CIA) model, as it shares hallmarks of human disease relevant for this study, such as the SF activation. As expected from previous studies ( 38 ), CIA SFs showed elevated cytokine production compared to naïve cells, corroborating their inflammatory phenotype. ARNO knock-down in such CIA cells reduced the IL-1β-dependent release of IL-6, CCL2 and MMP3, the latter also in a significant manner in these in vivo activated cells.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…We chose the Collagen-Induced Arthritis (CIA) model, as it shares hallmarks of human disease relevant for this study, such as the SF activation. As expected from previous studies ( 38 ), CIA SFs showed elevated cytokine production compared to naïve cells, corroborating their inflammatory phenotype. ARNO knock-down in such CIA cells reduced the IL-1β-dependent release of IL-6, CCL2 and MMP3, the latter also in a significant manner in these in vivo activated cells.…”
Section: Resultssupporting
confidence: 90%
“…To obtain further mechanistic insight, we investigated potential signaling pathways regulated by ARNO ( Figure 4 ). Thus, we explored the role of ARNO in the IL-1β STAT3 signalling pathway, as this can play key roles in both acute and chronic inflammatory responses upon IL-1β stimulation in SFs ( 38 ). We also evaluated the p38 MAPK pathway, as it has been shown to be important for RA pathogenesis and IL-1β signalling ( 39 ) and also for ARNO signaling in relation to MMP expression ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, and consistent with our wealth of data suggesting that ES-62 acts to resolve chronic inflammation rather than suppressing steady-state or “emergency” responses, it is possible that ES-62 only targets “hyper-responsive” cells, the cross-talk between signals generated by ES-62 and the pathogenic microenvironment generating a unique, modulated phenotype. Supporting this idea, whilst ES-62 similarly has little or no effect on the functionality of fibroblasts in the synovial joints of healthy mice, it induces a stable epigenetically rewired, inflammation-resolving/tissue repair phenotype of synovial fibroblast in mice undergoing collagen-induced arthritis (CIA; a model of rheumatoid arthritis), that is distinct from that found in naïve animals ( 65 ). Interestingly, IL-1β signalling, a key factor in driving the pathogenic transformation of synovial fibroblasts in CIA and rheumatoid arthritis that is targeted by ES-62 ( 65 ), is crucial to the pro-inflammatory training of both BM and migratory “surveillance” haemopoietic stem and progenitor cells (HSCPs) and their resultant accumulation and differentiation into adipose tissue-resident myeloid cells that perpetuates the inflammatory osteoimmunology cycle in obesity ( 24 , 66 68 ).…”
Section: Discussionmentioning
confidence: 99%